Differential Subordination and Superordination of Analytic Functions Defined by Cho-Kwon-Srivastava Operator (Global Journal of Science Frontier Research, 2012)
Differential subordination and superordination results are obtained for analytic functions in the open unit disk which are associated with Cho-Kwon-Srivastava operator. These results are obtained by investigating appropriate classes of admissible functions. Some of the result established in this paper would provide extensions of those given in earlier works.
Keywords: Analytic functions; integral operator; hadmard product; differential subordination; super - ordination